Atmospheric curing of zinc sulfide concentrate by sulfuric acid below 300°C - Deng F.-L.; Xu G.-X.; Fan W.-W.; Li S.; Ma R.-X. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Because the traditional roasting-leaching-electrowinning zinc hydrometallurgy process has a small sulfuric acid sales radius and a high inventory pressure, the process of direct leaching zinc concentrate is gaining popularity, but the pressurized leaching process is a high-pressure condition, which requires strict equipment material and high safety requirements. Furthermore, the atmospheric leaching efficiency is low and generally introduces impurities and chloride ions, which increase the cost of subsequent decontamination. Therefore, a new environmentally friendly hydrometallurgy extraction method of zinc was proposed: an atmospheric pressure medium temperature sulfuric acid curing-leaching process. Under open-air conditions, zinc sulfide concentrate was cured with sulfuric acid at different acid-to-ore ratios and heated to 220℃~260℃ for a different time, then the cured product was leached. The effects of temperature, curing time, acid-to-ore ratio, and sulfuric acid concentration on the leaching ratio of zinc (ηZn) were studied. The results demonstrated that ηZn could reach as high as 98.23% under the optimized conditions of temperature 240℃, curing time 2.5 hours, acidto-ore ratio 1.4:1, and sulfuric acid concentration 60 wt.%. The leaching residue ratio is 6%, with silicate accounting for the majority of it. The kinetic results support the shrinking core model, which is controlled by an interface chemical reaction with an apparent activation energy of 43.158 kJ/mol.